Proximate Analysis of Donuts Substituted with Corn Cob Flour (Zea mays) - Sufrotun Khasanah; Mahfud Nugroho; Fitria Yuni Astuti (G-Tech: Jurnal Teknologi Terapan, 2025)
Corn cobs are agricultural waste that contain nutrients that are good for humans. Corn cobs have high crude fiber, so they are good for health and safe to consume. One of them that can be used as a processed food product is donuts. Wheat flour is the raw material for making donuts, which is imported from various countries. Therefore, the use of wheat flour must be reduced by focusing on components that are abundant in Indonesia and have high nutritional content. The aim of this research is to analyze nearby donuts produced from wheat flour substituted for corn cob flour. Donuts were made with varying concentrations of 5%, 10%, and 15% corncob flour addition. The parameters tested in proximate analysis are water content, ash content, protein, fat, and carbohydrates. The research results showed that the values ​​of water content, ash content, protein, and fat tended to increase along with increasing the number of corn cobs in the donut formulation. Meanwhile, the carbohydrate content decreases with increasing corncob flour. This donut proximate analysis is in accordance with SNI 01-2000 standards. Donuts made with a higher percentage of corncob flour will be tastier.